Disruption by AI and No-Code Platforms on Traditional IT Business Models: Challenges and Entrepreneurial Opportunities - Muhamad Sabil Fausta; Herbert Siregar; Madelyne Angelica (Research Synergy Foundation, 2026)
Disruption brought by Artificial Intelligence (AI) and No-Code/Low-Code (NCLC) platforms has significantly transformed traditional business models in the Information Technology (IT) industry. These technologies are not only reshaping software development methods but also redefining value creation frameworks and entrepreneurial trajectories. This study aims to identify key adaptation challenges and entrepreneurial opportunities resulting from these shifts. Through a systematic literature review of 22 Scopus-indexed publications, the study reveals that IT firms face critical issues including workforce reskilling, shifts in revenue models, and organizational resistance to change. Simultaneously, new opportunities arise in areas such as AI consultancy services, tailored NCLC platform development, and disruptive product innovation. By synthesizing the implications of AI and NCLC disruptions, this paper provides strategic insights for academics and practitioners seeking to navigate and leverage digital transformation in emerging digital markets, with a particular focus on small and medium-sized enterprises (SMEs) across Southeast Asia.